EPISTEMOLOGI FILSAFAT DAN TASAWUF DALAM TRADISI KEILMUAN ISLAM: IMPLIKASINYA DALAM PEMBENTUKAN PENDIDIKAN ISLAM YANG HOLISTIS - Khoirun Nisaa; Nuriyatul Qomariyah; Muhammad In’am Esha; Imron Rossidy (STKIP Subang, 2026)
This study aims to examine the concepts of philosophical epistemology and Sufism in the Islamic scientific tradition, analyze the integration patterns between the two, and identify their implications for the formation of holistic Islamic education. This research is motivated by the dichotomy between rational and spiritual approaches to knowledge, which has resulted in the separation of religious knowledge and general knowledge in the Islamic education system. The method used is qualitative research with a library research approach, with content analysis techniques for books, scientific journals, and relevant literature. The results of the study indicate that first, philosophical epistemology (burhani) places reason as an instrument of rational verification. Second, Sufism epistemology (irfani) emphasizes intuition, inner experience, and purification of the soul as a path to acquiring hudhuri knowledge. Third, the integration pattern between philosophical epistemology (burhani) and Sufism (irfani) shows that these two approaches are complementary, not contradictory, where reason verifies concepts while inner experience absorbs the essence of reality. Fourth, this integration has comprehensive implications for the formation of holistic Islamic education, both ontologically, epistemologically, methodologically, and axiologically. This integration has implications for the ontological, epistemological, methodological, and axiological aspects of Islamic education, so that education is directed toward a balance between the intellectual intelligence and spiritual maturity of students.